Evaluation of an in vitro coronary stent thrombosis model for preclinical assessment. (17th February 2020) - Perry-Nguyen, Dylan; Jung, Richard G.; Labinaz, Alisha; Duchez, Anne-Claire; Dewidar, Omar; Simard, Trevor; Karunakaran, Denuja; Majeed, Kamran; Sarathy, Kiran; Li, Ruonan; Ramirez, F. Daniel; Di Santo, Pietro; et al.
Abstract: Stent thrombosis remains an infrequent but significant complication following percutaneous coronary intervention. Preclinical models to rapidly screen and validate therapeutic compounds for efficacy are lacking. Herein, we describe a reproducible, high throughput and cost-effective method to evaluate candidate therapeutics and devices for either treatment or propensity to develop stent thrombosis in an in vitro bench-top model. Increasing degree of stent malapposition (0.00 mm, 0.10 mm, 0.25 mm and 0.50 mm) was associated with increasing thrombosis and luminal area occlusion (4.1 ± 0.5%, 6.3 ± 0.5%, 19.7 ± 4.5%, and 92.6 ± 7.4%, p < 0.0001, respectively). Differences in stent design in the form of bare-metal, drug-eluting, and bioresorbable vascular scaffolds demonstrated differences in stent thrombus burden (14.7 ± 3.8% vs. 20.5 ± 3.1% vs. 86.8 ± 5.3%, p < 0.01, respectively). Finally, thrombus burden was significantly reduced when healthy blood samples were incubated with Heparin, ASA/Ticagrelor (DAPT), and Heparin+DAPT compared to control (DMSO) at 4.1 ± 0.6%, 6.9 ± 1.7%, 4.5 ± 1.2%, and 12.1 ± 1.8%, respectively (p < 0.01). The reported model produces high throughput reproducible thrombosis results across a spectrum of antithrombotic agents, stent design, and degrees of apposition. Importantly, performance recapitulates clinical observations of antiplatelet/antithrombotic regimens as well as device and deployment characteristics. Accordingly, this model may serve as a screening tool for candidate therapies in preclinical evaluation.